Earlier onset of North Atlantic hurricane season with warming oceans - Truchelut, Ryan E.; Klotzbach, Philip J.; Staehling, Erica M.; Wood, Kimberly M.; Halperin, Daniel J.; Schreck, Carl J.; Blake, Eric S. (Nature communications, 2022)
Numerous Atlantic basin tropical cyclones have recently developed prior to the official start of hurricane season, including several pre-season landfalls in the continental United States. Pre-season and early-season tropical cyclones disproportionately affect populated landmasses, often producing outsized precipitation impacts. Here we show a significant trend towards earlier onset of tropical cyclone activity in the North Atlantic basin, with threshold dates of the first three percentiles of accumulated cyclone energy shifting earlier at a rate exceeding five days decade −1 since 1979, even correcting for biases in climatology due to increased detection of short-lived storms. Initial threshold dates of continental United States named storm landfalls have trended earlier by two days decade −1 since 1900. The trend towards additional pre-season and early-season activity is linked to spring thermodynamic conditions becoming more conducive for tropical cyclone formation. Genesis potential index value increases in the western Atlantic basin are primarily driven by warming ocean temperatures. There is a significant trend in recent decades towards an earlier start to North Atlantic hurricane seasons. Both the first named storm and first U.S. landfall of the year are occurring earlier. This shift is physically linked to warmer western North Atlantic sea surface temperatures in spring.